FM research in Switzerland. Issue 1 (28th January 2014) - Windlinger, Lukas; Hofer, Susanne; Coenen, Christian; Honegger, Franziska; von Felten, Daniel; Kofler, Andrea; Wehrmüller, Thomas
Abstract : Purpose: – This paper aims to review FM research in Switzerland with a focus on recent research projects at the Institute of Facility Management of the Zurich University of Applied Sciences. Design/methodology/approach: – The paper provides a summary and review of research projects. Findings: – FM research in Switzerland has grown in the past few years and is now well rooted in the Swiss FM industry. The focus is on service management, workplace management and FM in health care. FM research in Switzerland has been driven collaboratively by the Institute of FM and the industry. Research limitations/implications: – Research at the IFM is very much oriented towards application and many collaborative projects between industry, public administration and universities have been conducted. However, some fields of FM have received little attention yet. Practical implications: – FM research in Switzerland has been driven collaboratively by the Institute of FM and the industry. The focus is on application, e.g. management tools, benchmarking systems or the relationship of FM services, organisational outcomes, and customer satisfaction. Many research results contribute to the development of Swiss FM industry. Originality/value: – In this article the authors summarize FM research in Switzerland and their research approach. With this they contribute to transparency and further development of FM research.